The consequences of emerging cash crops on small-scale rural farmers' livelihoods : a case study of the energy crop, Jatropha Curcas L, in Kenya : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Wamalwa, Joshua Kizito (Massey University, 2011)
This thesis investigates claims that growing of drought resistant cash crops such as Jatropha Curcas L (Jatropha) by small-scale rural farmers living in arid and semi-arid regions is an effective way to improve their livelihoods through increased income and improved food security. One school of thought supports this claim – often made by proponents of the bio-fuel industry - and another is sceptical about the claim. This research used the Sustainable Livelihoods Framework to evaluate the impact of growing Jatropha on the livelihoods of smallscale rural farmers in the Meru North district in Kenya. The findings revealed that, some elements of Jatropha farming as an agricultural strategy could be capable of improving rural livelihoods. Interviews carried out with farmers showed that Jatropha growing has had positive and negative impacts on the farmers’ livelihoods. Farmers - especially those who were also traders in Jatropha - noted significant positive impacts in their financial, physical, human, and natural capital domains as demonstrated in the asset pentagon. However, the impacts were far less positive for those farmers who only produced Jatropha. Positive impacts of Jatropha were also noted amongst the wider rural communities. Local people interviewed indicated that Jatropha growing has increased their access to job opportunities as farmers were now employing local people on a casual basis to help out on the Jatropha farms. The local people including farmers have also used the Jatropha plant as a soil protector in places where land is susceptible to soil erosion and mud slides in the region. There were some fundamentals of rural livelihoods that did not experience any immediate impact as a result of Jatropha farming. For instance, food production has not been impacted upon negatively as expected. Food supply in the region has remained constant due to the modes of Jatropha production adopted by farmers that do not interfere with the production of food crops. Similarly, no evidence was found that Jatropha growing had impacted positively or negatively on communal or state-owned physical capital assets. Negative impacts were however noted in the social capital domains of farmers, as many farmers who produced Jatropha but did not trade it themselves have lost trust in their neighbours who acted as their middlemen or traders. More so, this study concludes that the expansion of the Jatropha trade has increased inequality among farmers. Farmers who are ii presumed to be the poorest in the region are not taking up the growing of Jatropha, therefore the benefits of growing Jatropha are only being tapped by the richer farmers. In addition this thesis concludes that growing of Jatropha has increased labour demand for family members and particularly women are bearing much of the heavy labour impact in households in rural areas.
Keywords: Cash crops; Jatropha Curcas L; Sustainable Livelihood Frameworks; Economic aspects; Rural communities; Rural development; Farming; Farmers; Labour demand